Medicago truncatula Phytoglobin 1.1 controls symbiotic nodulation and nitrogen fixation via the regulation of nitric oxide concentration. Issue 1 (14th March 2020) - Berger, Antoine; Guinand, Sophie; Boscari, Alexandre; Puppo, Alain; Brouquisse, Renaud
Summary: In legumes, phytoglobins (Phytogbs) are known to regulate nitric oxide (NO) during early phase of the nitrogen‐fixing symbiosis and to buffer oxygen in functioning nodules. However, their expression profile and respective role in NO control at each stage of the symbiosis remain little‐known. We first surveyed the Phytogb genes occurring in Medicago truncatula genome. We analyzed their expression pattern and NO production from inoculation with Sinorhizobium meliloti up to 8 wk post‐inoculation. Finally, using overexpression and silencing strategy, we addressed the role of the Phytogb1.1‐NO couple in the symbiosis. Three peaks of Phytogb expression and NO production were detected during the symbiotic process. NO upregulates Phytogbs1 expression and downregulates Lbs and Phytogbs3 ones. Phytogb1.1 silencing and overexpression experiments reveal that Phytogb1.1‐NO couple controls the progression of the symbiosis: high NO concentration promotes defense responses and nodular organogenesis, whereas low NO promotes the infection process and nodular development. Both NO excess and deficiency provoke a 30% inhibition of nodule establishment. In mature nodules, Phytogb1.1 regulates NO to limit its toxic effects while allowing the functioning of Phytogb‐NO respiration to maintain the energetic state. This work highlights the regulatory role played by Phytogb1.1–NO couple in the successive stages of symbiosis. Abstract : See also the Commentary on this article by Singh et al ., 227 : 5–7 .